The influence of store environment on consumer purchasing behavior in supermarket - Kong Mei Yee; Muhamad Hafizuddin Khusini; Noorsyazana Ishak; Nor Hidayah Ismail (2016)
Previous studies found that store environment has significant relationship towards consumer purchasing behavior. But most of these research might not accurate for the implementation in the supermarket retailers. Therefore, the purpose of this study was to identify the influence of the store environment’s elements on consumer purchasing behavior in supermarket. The elements investigate were music, lighting, layout and store density that were selected and justified by researchers from literature review. This study was conducted by using quantitative research approach with a total of 384 respondents involves in this study. The respondents were selected by using a convenience sampling method among the people who live in Kota Bharu, Kelantan. This study analyzed the data by using the Statistical Package for Social Science (SPSS) software version 22. Data analysis was doe for the normality test, reliability analysis, descriptive analysis, univariate analysis, Pearson correlation analysis, and multiple linear regression analysis. The results showed that all the elements had significant relationships with consumer purchasing behavior. But, only music and lighting are statistically significant influence the consumer purchasing behavior in supermarket at Kota Bharu, Kelantan. The layout and store density, however, had not significantly influence the consumer purchasing behavior in supermarket. Accordingly, music was found to be dominant predictor that influence consumer purchasing behavior in supermarket, and followed by lighting. This research contributes for practical implications for the supermarket retailers especially the supermarket in Kota Bharu, Kelantan to improve their store environment that could lead to the increment of purchasing and sales.